Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1046/j.1468-2982.2001.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘dry-needle technique’: intramuscular stimulation in tension-type headache

Abstract: The 'dry-needle technique', an intramuscular stimulation technique carried out by using a fine solid, 1-inch long, 30-gauge needle, was investigated in the treatment of tension-type headache (TTH) in a randomized, placebo-controlled trial. Fifteen patients with TTH received intramuscular needle insertions into six designated trigger points, while 15 controls received subcutaneous insertions. Headache indices, muscle tenderness and neck ROMs were evaluated before and after treatment. Mean headache indices impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 6 publications
3
56
0
3
Order By: Relevance
“…Effects found in this study that have been previously reported include: differences between acupuncture and control for migraine 7,12,45 that increased between posttreatment and 1-year follow-up, 11 unconvincing effects for tension-type headache, [46][47][48][49] improvements in severity and frequency, 24 and increased benefit in patients with greater headache severity.…”
Section: Comparison With Other Studiessupporting
confidence: 65%
“…Effects found in this study that have been previously reported include: differences between acupuncture and control for migraine 7,12,45 that increased between posttreatment and 1-year follow-up, 11 unconvincing effects for tension-type headache, [46][47][48][49] improvements in severity and frequency, 24 and increased benefit in patients with greater headache severity.…”
Section: Comparison With Other Studiessupporting
confidence: 65%
“…Another RCT suggested that deep needling of MFTrPs might be more effective than traditional acupuncture or superficial trigger point needling in the treatment of chronic LBP in the elderly 140 . However, only two studies have looked at the effect of TrPDN on various headache forms 93,127 . One RCT that compared dry needling of MFTrPs in the neck and metoprolol in migraine prophylaxis for the treatment of MH found a significant reduction in headache frequency (P<0.01) for both groups and no between-group difference in frequency or duration 136 .…”
Section: Discussionmentioning
confidence: 99%
“…One RCT that compared dry needling of MFTrPs in the neck and metoprolol in migraine prophylaxis for the treatment of MH found a significant reduction in headache frequency (P<0.01) for both groups and no between-group difference in frequency or duration 136 . The second RCT study-albeit one with a small sample size-looked at the effect of dry needling on TTH and found a significant improvement in headache indices, tenderness score, and neck mobility limitation 93 . With regard to the research basis on the efficacy of OMPT, massage therapy has been deemed effective in the treatment of LBP due to MFTrPs 144 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The effects of acupuncture on various types of headache have been studied widely. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In a Cochrane review, Melchart et al compared the effectiveness of acupuncture with 'sham' (placebo) acupuncture and other interventions used to treat idiopathic (primary) headaches including tensiontype headache. 3 They concluded that the evidence supports the role of acupuncture for the treatment of idiopathic headaches but is not conclusive.…”
Section: Introductionmentioning
confidence: 99%